Design Of A Horizontal Conveyor System For Scrap Rubber In FGV Pasir Besar - bin Mahamud, Muhammad Nazmi Izzuddin; Azlan, Mohd Azwir (Research Progress in Mechanical and Manufacturing Engineering, 2022)
In FGV Pasir Besar, scrap rubber are transported form the cutting section to the processing pool with a backhoe. The usage of a backhoe to transport the scrap rubbers contributes to a lower efficiency and production rate for the production line. The objectives for this project are to produce a complete design of a horizontal conveyor system that is able to transfer cast amount of scrap rubber that will help in reducing the logistical cost of transferring scrap rubber in rubber processing plant. Consequently, design processes that are proposed by George E. Dieter and Rudolph J. Eggert are altered and utilized. This design process provides the guide form problem definition to detail design of the system. Additionally, SolidWorks is utilized to produce engineering drawing and simulation to estimate the functionality of the system. The system that is developed is expected to carry up to 143 ton of scrap rubber per hour. The manufacturer also can extend their services from providing the particular components to providing multiple components so that the components that are used in the conveyor system can be easily chosen and invariable.